Explorasi Mikroba Beraroma dari Bahan Alam - Prapti Sedijani; Dewa Ayu Citra Rasmi; Syamsul Bahri (Jurnal Penelitian Pendidikan IPA, 2019)
Abstract: The Scented volatile compound has a huge market as its wide applications in daily life. The extraction of this compound from natural resources produces a very low rendement. Microbes synthesize secondary metabolit might resemble of their host have been explored from scented natural resources (flowers: Damask rose, Jasminum sambac and Plumeria acutifolia); cymbopogon, muntinga calabura L and leave of Panadus amaryllis).  It was found 12 bacterial and 14 fungal scented isolates that were various in terms of scent types and intensities. They were bread starters like the smell, alcohol like the smell, sweet sugar like the smell, salaka like the smell and fresh sugarcane juice like smell. Several isolates emit original host like the smell in very low intensities. Persistency scent test showed that the scents were persistently emitted when cultured on PDA medium.  Key Words: Scented volatile; Damask rose; microba; exsplorasi